Effect of supplementation of wheat bran on dough aeration and final bread volume. (July 2019) - Packkia-Doss, Paulin Patricia; Chevallier, Sylvie; Pare, Akash; Le-Bail, Alain
Abstract: One of the best ways to increase the fiber content in the diet is supplementing wheat bran in bread. Wheat bran is known to affect the cellular structure of the dough, resulting in lower final bread volume. The present study was focused on analyzing the effect of wheat bran in throughout the bread making process; the results were compared with the recipe without bran. Wheat bran at different level viz., 0%, 8%, 16% and 24% w/w on flour basis was added into the wheat flour for the preparation of sandwich bread. Results showed that wheat bran significantly (p < 0.05) affected the dough kneading parameters. Dough properties like stickiness and extensibility decreased with respect to increase in bran quantity. Unexpectedly, wheat bran enhanced the aeration of dough during mixing and the expansion rate of dough during fermentation. However, wheat bran decreased the specific volume of bread upto 10.81%, which was confirmed using 2D image analysis method where it was observed as the wheat bran alters the pore size distribution in bread crumb. Highlights: Wheat bran improves the fiber content of the sandwich bread and affects dough and bread properties. Effect of wheat bran on carbon dioxide release was studied by measuring expansion rate of dough during fermentation. Dough rheological properties with and without addition of bran were studied to quantify its effect on dough. Wheat bran at higher level significantly increased the dough development time and porosity. Image analysis was carried out to find the effect of bran on pore area distribution in bread crumb.